The Relationship between Mother's Motivation and the Implementation of Post SC Early Mobilization at RSIA Muhammadiyah Probolinggo City in 2022 - Nurkhoniyah, Siti; Hanifah, Iis; Natalia, Mega Silvian (NHM PRESS, 2023)
Labor is the process of expulsion of the fetus at term pregnancy. Meanwhile, Sectio caesarea (SC) delivery is carried out by making incisions in the abdomen and uterus of pregnant women to help the process of expelling the baby from the womb. After the SC procedure, the patient is advised to perform early mobilization. The mobilization carried out by the mother needs a strong motivation, both intrinsic and extrinsic. The purpose of this study was to analyze the relationship between mother's motivation and the implementation of early post SC mobilization at RSIA Muhammadiyah Probolinggo City. This study uses a correlational analysis design with a cross sectional approach. The sample data were post SC mothers at RSIA Muhammadiyah Probolinggo City during April-June who met the inclusion criteria with accidental sampling technique. Data collection includes, coding, editing, and tabulating which then the data is analyzed by computer with the Spearman test p value: 0.05. The results showed that respondents had high motivation of 28 respondents (48.3%), respondents carried out early mobilization by 28 respondents (48.3%) and p value: 0.000. The conclusion of the study is that there is a relationship between maternal motivation and the implementation of early post SC mobilization at RSIA Muhammadiyah Probolinggo City (p = 0.000 <0.05). The suggestion put forward is that it is hoped that hospitals can make policies by always updating health promotion media materials, especially about early mobilization both printed and electronic, so that post SC mothers understand and have the courage to do early mobilization.